An in vivo pathway for disulfide bond isomerization in Escherichia coli - Rietsch, Arne (The National Academy of Sciences of the USA, 1996)
Biochemical studies have shown that the periplasmic protein disulfide oxidoreductase DsbC can isomerize aberrant disulfide bonds. Here we present the first evidence for an in vivo role of DsbC in disulfide bond isomerization. Furthermore, our data suggest that the enzymes DsbA and DsbC play distinct roles in the cell in disulfide bond formation and isomerization, respectively. We have shown that mutants in dsbC display a defect in disulfide bond formation specific for proteins with multiple disulfide bonds. The defect can be complemented by the addition of reduced dithiothreitol to the medium, suggesting that absence of DsbC results in accumulation of misoxidized proteins. Mutations in the dipZ and trxA genes have similar phenotypes. We propose that DipZ, a cytoplasmic membrane protein with a thioredoxin-like domain, and thioredoxin, the product of the trxA gene, are components of a pathway for maintaining DsbC active as a protein disulfide bond isomerase.